PENGEMBANGAN MODUL EFIKASI DIRI DALAM MENGHADAPI PERSALINAN NORMAL BERBASIS KARIKATUR DALAM MENINGKATKAN PENGETAHUAN IBU HAMIL - Jumrah; Julia Fitrianingsih; SR, Nurqalbi; Sumarni; Rosita (Jurnal Ilmiah Kebidanan Imelda, 2023)
The incidence of childbirth complications itself is a determinant of maternal morbidity and mortality. The importance of preparation is carried out as a program of instruction with a specific purpose and structure. Birth preparation aims to prepare all the needs during pregnancy and childbirth. Mother's self-efficacy can describe the ability to go through the birth process well. This is an important factor influencing women's motivation to give birth normally. This study aims to develop a caricature-based module to increase mothers' self-efficacy in dealing with normal delivery. The design used in this study is the R & D (Research and Development) method through 5 stages. After developing the module, a product trial was carried out using the Pilot Study. The number of participants in the module trial was 20 participants who were Trimester II and Trimester III pregnant women. Data analysis was carried out by descriptive and paired T-test. The results of the research show that development has been carried out through literature studies and focus group discussions (FGD) with the stages of material validation by 4 material experts and 2 media experts, where the results of the posttest module trial score were 81.04. The increase in knowledge before and after education is 24.99. This shows that the developed module can increase mother's knowledge. The developed module can be used by pregnant women to increase knowledge that will support the increase in the mother's self-efficacy in dealing with childbirth.